The chimerical genome of Isla del Coco feral pigs (Costa Rica), an isolated population since 1793 but with remarkable levels of diversity. Issue 10 (22nd April 2015) - Bianco, E.; Soto, H. W.; Vargas, L.; Pérez‐Enciso, M.
Abstract: The history of domestic species and of their wild ancestors is not a simple one, and feral processes can clarify key aspects of this history, including the adaptive processes triggered by new environments. Here, we provide a comprehensive genomic study of Isla del Coco (Costa Rica) feral pigs, a unique population that was allegedly founded by two individuals and has remained isolated since 1793. Using SNP arrays and genome sequencing, we show that Cocos pigs are hybrids between Asian and European pigs, as are modern international pig breeds. This conclusively shows that, as early as the 18th century, British vessels were loading crossbred pigs in Great Britain and transporting them overseas. We find that the Y chromosome has Asian origin, which has not been reported in any international pig breed. Chinese haplotypes seem to have been transmitted independently between Cocos and other pig breeds, suggesting independent introgression events and a complex pattern of admixing. Although data are compatible with a founder population of N  = 2, variability levels are as high in Cocos pigs as in international pig breeds (~1.9 SNPs/kb) and higher than in European wild boars or local breeds (~1.7 SNPs/kb). Nevertheless, we also report a 10‐Mb region with a marked decrease in variability across all samples that contains four genes ( CPE, H3F3C, SC4MOL and KHL2 ) previously identified as highly differentiated between wild and domestic pigs. This work therefore illustrates how feral population genomic studies can help to resolve the history of domestic species and associated admixture events.